Uji Diagnostik Ekspresi CK19 dan HBME-1 pada Lesi Jinak dan Ganas Tiroid - Indah Yati; Henny Sulastri; Aspitriani (Majalah Patologi Indonesia, 2021)
BackgroundThyroid carcinoma is the most common malignancy of the endocrine system. Some cases histopathologically have overlappingmorphological features among papillary thyroid carcinoma follicular variants and follicular adenomas; beetween nodular hyperplasiaand protruding papillary protrusion; nuclear feature and thyroid papillary carcinoma. The combination of CK19 and HBME-1imunohistochemical staining have been proven as specific and sensitive markers to distinguish benign and malignant lesions thyroid.The purpose of this study was to determine the differences in CK19 and HBME-1 expression in benign and malignant Thyroid lesions.MethodsThis study used a diagnostic test of 50 cases (16 cases of nodular hyperplasia, 8 cases of follicular adenoma, 21 papillary thyroidcarcinomas and 5 cases of thyroid follicular carcinoma) clinicopathological data were noted. Immunohistochemical staining wasperformed using CK19 and HBME-1antibodies and the their expression assessed. Data were analysed by SPSS version 22.0.ResultsBased on the four histopathological diagnoses, the majority patient, were females between 20-50 years.Fifty percent of macroscopicsample size was more than 5 cm. The expression of CK19 and HBME-1 has a sensitivity value of 76.9% and 92.3% and a specificityvalue of 79.2% and 79.2%, consecutively. While positive predictive value 80% and 82.8% and negative predictive value 76% and90.5%, accuracy of 78% and 86%, respectively.ConclusionHBME-1 expression could be used to distinguishing benign from malignan lesions of thyroid with high diagnostic sensitivity thanCK19 expression.